Efektivitas Relaksasi Autogenik dalam Mengurangi Gangguan Kecemasan Mengerjakan Skripsi: Tinjauan Komprehensif dan Meta-Analisis - Yulfikasari Linggi Bandaso; Ahmad Ridfah; Ismalandari Ismail (IDEA: Jurnal Psikologi, 2026)
This study examined the effect of autogenic relaxation on thesis-related anxiety among final-year students at Universitas Negeri Makassar. A quasi-experimental one-group pretest-pottest design with follow-up was employed, involving five female students (aged 21-23) who reported high levels of anxiety. Anxiety was assessed using a scale developed from Blackburn and Davidson’s framework, administered before the interventi (pre-test), one week after (post-test), and two weeks later (follow-up). Friedman test results indicated a significant reduction in anxiety across the three measurements ( (2)=9.57;p<0.05). Post-hoc Wilcoxon tests confirmed significant decreases from pre-test to post-test, post-test to follow-up, and pre-test to follow-up (all p<0.05). These findings suggest that autogenic relaxation is effective in reducing thesis-related anxiety and may serve practical self-coping strategy for students. Despite the small sample size bering a limitation, the results provide premilinary evidence for incorporating relaxation-based programs into campus couseling services to support student well-being.